Final-year students’ perceptions of online integrated primary care learning - Aviva Ruch; Joel Francis; Ann Z. George (South African Family Practice)
Background: Integrated primary care (IPC) is a final-year medical subject at the University of the Witwatersrand, Johannesburg, South Africa. It focusses on primary health care training. The coronavirus disease 2019 (COVID-19) pandemic exacerbated existing decentralised training challenges, including standardisation and patient exposure. This study explored IPC students’ experiences and perceptions of online learning during the COVID-19 pandemic.